System ekonomiczno-finansowy a system rachunkowości w zarządzaniu jednostką - teoria a praktyka - Gad, Jacek; Walińska, Ewa (Entity Economic-Financial System and Accounting System - Theory and Practice, 2008)
Economic-financial system is the specific term not defined precisely in the literature. The article deals with individual entity accounting system and its relation to entity economic-financial system. The main purpose of this article is to present some solutions existing in current practice of some Polish companies, especially in the documentation issue. It is very interesting from the research point of view whether internal regulations in this area are useful and if the overall framework in this matter should be prepared for use and practice. As usually we can indicate two opposite results of each approach. On one side, introduction of any regulations in companies is treated as limitation of management freedom, but on the other, decision making process is easier and more effective.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (6); 2008; nr 1196, s. 33-47